Preparing for physical literacy: Exploring pre-service teachers' training and understanding. (December 2022) - Stoddart, Alexandra L.; Selanders, Katelyn P.
Abstract: Research has indicated some pre-service teachers have a poor understanding of physical literacy. As pre-service teachers will be expected to assist their future students in developing physical literacy, it is imperative that they are trained and supported to do so. This Canadian explanatory sequential study explored how pre-service teachers understand physical literacy, its place in the physical education curriculum, and whether more support is needed during their teacher preparation program. Data collection occurred in one province during 2018–2021. Phase 1 of the study included 51 participants, with six participants engaged in follow-up interviews in Phase 2. The Phase 1 analysis included chi-square analyses and frequency tabulations. Phase 2 data was analyzed using thematic analysis. Findings suggest that pre-service teachers are aware of physical literacy but need more support from Physical Education Teacher Education programs to authentically bring physical literacy to life.